Unseen ebook - Slaughter, Karin (Will Trent, 2013)
NEW YORK TIMES BESTSELLER • Detectives, lovers, and enemies face off in an unforgettable battle between righteous courage and deepest evil, from “one of the best crime novelists in America” ( The Washington Post ). WATCH WILL TRENT ON ABC • “Compelling . . . Slaughter balances a complex plot with believable twists while sensitively exploring her realistic characters’ emotions and problems.”— South Florida Sun-Sentinel With the bonus story “Busted”   Will Trent is a Georgia Bureau of Investigation agent, working undercover in Macon, Georgia, posing as Bill Black, a scary ex-con who trails an air of violence wherever he goes. The cover has worked and he has caught the eye of a wiry little drug dealer who thinks he might be a useful ally.    But there’s a problem. Cut off from the support of the woman he loves, Sara Linton, Will finds his demons catching up with him.    Although she has no idea where Will has gone, or why, Sara herself has come to Macon because of a cop shooting. Her stepson, Jared, has been gunned down. Suddenly, without even knowing it, Sara finds herself involved in the same case that Will is working—with danger swirling around both of them.    A novel of fierce intensity, shifting allegiances, and shocking twists, Unseen is an electrifying thriller and a piercing study of human nature: what happens when good people face the unseen evils in their lives.